Comparison of Lipid Profile in Type-2 Obese Diabetics and Obese Non-diabetic Individuals. A hospital Based Study from Western Nepal - Yadav, Naval Kishor; Thanpari, C; Shrewastwa, MK; Mittal, RK (Kathmandu University Medical Journal, 2013)
Background Type-2 diabetes mellitus is an independent risk factor for coronary artery disease and risk of coronary disease is three to four fold increased in patients with diabetes compared with non-diabetic population and 60-80% 0f type-2 diabetics are obese. Methods This study was conducted in Nepalgunj Teaching Hospital, Kohalpur, Banke, Nepal, between 1st March, 2011 and 28th February, 2012. A total of 150 samples were taken to assess the lipid profile in type-2 diabetic patients associated with obesity and 25 obese controls for their lipid profile. Venous blood samples were taken from all the subjects in the morning after fasting overnight. Exclusion criteria included pregnancy, chronic infectious disease, heart failure; renal failure and drug allergy were confirmed from the subject’s personal physician report and a detailed history. The data was analyzed using Excel 2003, R 2.8.0 Statistical Package for the Social Sciences (SPSS) for Windows Version 16.0 (SPSS Inc; Chicago, IL, USA) and the EPI Info 3.5.1 Windows Version. Results The mean ± SD age of diabetic patients with obesity was 53.76 ± 6.23 while the mean ± SD age of control was 49.61 ± 4.8. Out of 150 patients 105 (70%) were males and 45 (30%) were females. Among control subjects 16 (64%) were males and 9 (36%) were females. Obese type-2 diabetic patients when compared to obese control subjects showed statistically significant increase in the levels of serum total cholesterol (p ? 0.001), serum triglycerides (p ? 0.001), serum LDL-cholesterol (p ? 0.001) while serum HDL-cholesterol levels did not show statistically significant difference in the two group (p ? 0.05). Conclusion This study showed obese diabetic individuals have dyslipidemia and more prone to develop cardiovascular diseases. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 44-47 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8017